Bridging Trust and Capital for Islamic Cooperatives: Challenges and Opportunities in Rural Islamic Communities in Indonesia - Abdul Hakim; Fauziah Andriani; Tiara Amelia Ayu Utami; Faris Husein Pranata; Fadia Al Aulia Sundawa; Ahmad Sahidudin; Chelsy Kamei Fadillah (Journal of Islamic Economics and Business, 2025)
This study examines the dynamics of cooperative development in Wanasari Village, Sumedang Regency, with a focus on the interaction between women's groups, agricultural collectives, community trust, capital mobilization, and participatory education. The main issue raised is why many cooperatives in rural Indonesia are difficult to form and maintain. The uniqueness of this research lies in the integration of gender-based approaches and participatory education that are rarely empirically studied in rural contexts. The research uses a qualitative approach through Participatory Rural Appraisal (PRA), focused group discussions (FGDs), semi-structured interviews, field observations, and participatory SWOT analysis. The findings show that women's and peasant groups are actively promoting social cohesion and local economic activities, but are still faced with obstacles in the form of low community trust due to previous institutional failures, difficulties in mobilizing capital, and competition with Badan Usaha Milik Desa (BUMDes). Participatory education improves understanding of cooperatives, but it is not yet enough to overcome structural barriers. In conclusion, the formation of sustainable cooperatives requires continued participatory engagement, transparent governance, innovative financial strategies, and synergies with existing local entities.